Heliophysics: Space Storms and Radiation: Causes and Effects - Schrijver, Carolus J.; Siscoe, George L. (Cambridge : Cambridge University Press, 2010)
Heliophysics is a fast-developing scientific discipline that integrates studies of the Sun's variability, the surrounding heliosphere, and the environment and climate of planets. The Sun is a magnetically variable star and for planets with intrinsic magnetic fields, planets with atmospheres, or planets like Earth with both, there are profound consequences. This 2010 volume, the second in this series of three heliophysics texts, integrates the many aspects of space storms and the energetic radiation associated with them - from causes on the Sun to effects in planetary environments. It reviews the physical processes in solar flares and coronal mass ejections, interplanetary shocks, and particle acceleration and transport, and considers many space weather responses in geospace. In addition to its utility as a textbook, it also constitutes a foundational reference for researchers in fields from heliophysics to climate science. Additional online resources, including lecture presentations and other teaching materials, are available at www.cambridge.org/9780521760515.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Solar energetic particles; Heliosphere (Astrophysics); Solar wind